Pelatihan Perencanaan Karier untuk Kesiapan Kerja pada Siswa SMK Islam Anharul Ulum Blitar - Wahyuni, Veni; Pratiwi, Iqlima (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The community service program involves career planning training designed to enhance students' readiness for the workforce at SMKI Anharul Ulum Blitar. This location was chosen due to its connection with PT. Blitar Chocolate Village. Unemployment caused by inadequate career planning and work readiness can be mitigated through this socialization and training. The objective is to equip soon-to-graduate students with the knowledge and skills to develop comprehensive career plans, thus improving their future work readiness and reducing the risk of unemployment. The benefit of this initiative is that both students and the school gain insights into effective career planning, ensuring students are well-prepared for the workforce. As a result, SMKI Anharul Ulum Blitar students will be better informed about career planning and able to take proactive steps toward their future careers after graduation. Career planning is essential, particularly for vocational students, as it helps eliminate uncertainty when entering the job market and contributes to reducing unemployment.